Ethylbenzene dehydrogenation catalyst as well as preparation method and application thereof

By introducing CO32- and Ba/Sr elements into the ethylbenzene dehydrogenation catalyst, combined with specific preparation methods, the problems of more and low selectivity of existing catalysts are solved, and high styrene selectivity and high ethylbenzene conversion are achieved rate improves the economic benefits of reaction.

CN119259067AActive Publication Date: 2025-01-07CHINA PETROLEUM & CHEMICAL CORP +1
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202310822893.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-07-05
Publication Date
2025-01-07
Estimated Expiration
2043-07-05

AI Technical Summary

Technical Problem

The existing ethylbenzene dehydrogenation catalysts produce more by-products toluene and benzene in the reaction, and the styrene is not selective, resulting in increased material consumption and decreased economic benefits.

Method used

Provided is an ethylbenzene dehydrogenation catalyst including Fe, K, Ce, Mo, and Ca. The catalyst surface layer contains CO32-, which can improve the catalyst by adjusting the diffraction peak intensity with specific Raman spectral characteristic diffraction peak intensity, combining the synergistic action of Ba and Sr elements. performance. The method of preparing the catalyst includes using metal carbonate as a starting material, controlling the drying and calcining conditions to form an enriched CO32-surface structure.

Benefits of technology

The styrene selectivity and ethylbenzene conversion rate are significantly improved, the by-product generation is reduced, and the economic and efficiency of the reaction is improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119259067A_ABST
    Figure CN119259067A_ABST
Patent Text Reader

Abstract

The invention discloses an ethylbenzene dehydrogenation catalyst as well as a preparation method and application thereof. The catalyst comprises Fe, K, Ce, Mo, Ca and at least one selected from Ba and Sr; wherein the surface layer of the catalyst contains CO3 < 2->; in a Raman spectrum of the catalyst, the characteristic diffraction peak intensity of CO3 < 2-> is 10%-200% of the characteristic diffraction peak intensity of Fe2O3. The catalyst is used in styrene preparation reaction through ethylbenzene dehydrogenation, and has the advantages of high styrene selectivity and high ethylbenzene conversion rate.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of ethylbenzene dehydrogenation catalysts, and specifically relates to an ethylbenzene dehydrogenation catalyst and a preparation method and application thereof. Background Art

[0002] Styrene is an important monomer of polymers. It is mainly used as a monomer for the production of synthetic rubber and plastics, including expandable polystyrene, polystyrene and ABS (acrylonitrile-butadiene-styrene). Styrene is mainly produced by the catalytic dehydrogenation of ethylbenzene. This method uses ethylbenzene as a raw material and catalytically dehydrogenates it in the presence of steam to produce styrene. The catalyst plays a key role in the production of styrene by dehydrogenation of ethylbenzene. The performance of the catalyst determines the economic efficiency of the dehydrogenation process. Benzene and toluene are the main by-products of the dehydrogenation reaction of ethylbenzene. Reducing the production of toluene and benzene can improve the styrene selectivity of the reaction, reduce the material consumption of the device, and increase economic benefits.

[0003] Most of the existing ethylbenzene dehydrogenation catalysts are based on Fe-K-Ce series catalysts, in which Fe-K oxide is the main catalyst, Ce is the main auxiliary agent, and it also contains structural stabilizers and electronic auxiliary agents such as oxides of Mg, Mo, W and Ca. CN115487833A discloses an ethylbenzene dehydrogenation catalyst, which introduces at least one component of TeO2 and B2O3, In2O3 and Ga2O3 on the basis of Fe-K-Ce-Mo-Ca, and is used in the ethylbenzene dehydrogenation reaction to improve the selectivity of styrene. CN106582689A discloses a technical solution of adding In2O3 to a Fe-K-Ce-W-Mg-Ca catalyst system, and adding at least one of HfO2, Nb2O5 or Ta2O5, thereby improving the catalyst selectivity.

[0004] The catalysts in the prior art used in the dehydrogenation reaction of ethylbenzene all have the problems of producing more by-products of toluene and benzene and insufficient selectivity of styrene to varying degrees, resulting in increased material consumption and decreased economic benefits. Summary of the invention

[0005] The purpose of the present invention is to solve the problems of more by-products and lower styrene selectivity in the application of ethylbenzene dehydrogenation catalyst in the prior art, and to provide an ethylbenzene dehydrogenation catalyst and its preparation method and application. The catalyst is used in the reaction of ethylbenzene dehydrogenation to styrene, and has the advantages of high styrene selectivity and high ethylbenzene conversion rate.

[0006] The first aspect of the present invention provides an ethylbenzene dehydrogenation catalyst. The catalyst comprises Fe, K, Ce, Mo, Ca elements, and at least one selected from Ba and Sr; wherein the surface layer of the catalyst contains CO3 2- In the Raman spectrum of the catalyst, CO3 2-The intensity of the characteristic diffraction peak is 10% to 200% of the intensity of the characteristic diffraction peak of Fe2O3.

[0007] According to the present invention, in the Raman spectrum of the catalyst, CO3 2- The characteristic diffraction peak intensity is 10% to 200% of the characteristic diffraction peak intensity of Fe2O3. As a non-limiting example, CO3 2- The characteristic peak intensity is 15%, 20%, 30%, 40%, 50%, 60%, 70%, 78%, 90%, 100%, 110%, 120%, 130%, 150%, 180% etc. of the characteristic peak intensity of Fe2O3, and preferably 80% to 120%.

[0008] According to the present invention, the catalyst, based on the mass of the catalyst and calculated as oxide, comprises the following components:

[0009] (a) 60% to 83% Fe2O3;

[0010] (b) 8% to 20% K2O;

[0011] (c) 4% to 11% CeO2;

[0012] (d) 0.5% to 5% MoO3;

[0013] (e) 0.2% to 5% CaO;

[0014] (f) 0.1% to 2% of BaO and / or SrO.

[0015] According to the present invention, preferably, the catalyst composition includes both Ba and Sr elements. Further preferably, the mass ratio of BaO to SrO is 0.2 to 3:1, preferably 0.5 to 3:1, calculated as oxides. Ba and Sr have a synergistic effect in improving the styrene selectivity and ethylbenzene conversion rate of the catalyst in the ethylbenzene dehydrogenation reaction.

[0016] The second aspect of the present invention provides a method for preparing the ethylbenzene dehydrogenation catalyst, the method comprising the steps of:

[0017] The ethylbenzene dehydrogenation catalyst is obtained by mixing Fe source, K source, Ce source, Mo source, Ca source, at least one selected from Ba source and / or Sr source, and an optional pore former, and then drying, molding, and calcining.

[0018] According to the present invention, at least one of the catalyst raw material metal sources is a metal carbonate. 2- Derived from metal carbonates.

[0019] According to the present invention, no binder is added in the preparation method of the ethylbenzene dehydrogenation catalyst.

[0020] According to the present invention, a proper amount of water can be added during the molding process. The water addition method is slow addition, and the amount of water added is not particularly limited and can be adjusted according to the dryness and wetness of the material. Preferably, the amount of water added is 15% to 35% of the total weight of the catalyst raw material by mass.

[0021] According to the present invention, the forming can be performed by extrusion molding, and the strips can be particles with a diameter of 2 to 5 mm and a length of 3 to 10 mm.

[0022] According to the present invention, the drying conditions are: temperature 10-90°C, preferably 20-60°C; and / or time 0.5-10h, preferably 1-8h; and / or relative humidity 50%-100%, preferably 60%-99%.

[0023] According to the present invention, the calcination conditions are: a calcination temperature of 700 to 1000° C., preferably 750 to 950° C.; and / or a calcination time of 0.5 to 10 h, preferably 2 to 6 h.

[0024] According to the present invention, the catalyst raw material metal source is added in the form of metal salt and / or metal oxide. At least one of the catalyst raw material metal sources is a metal carbonate.

[0025] According to the present invention, preferably, the Fe source is added in the form of oxide Fe2O3. The Fe source is preferably selected from red iron oxide and / or yellow iron oxide. The K source is potassium carbonate. The Ce source is added in the form of cerium salt; the cerium salt is any one or more of cerium nitrate, cerium oxalate, and cerium carbonate. The Mo source is added in the form of molybdenum salt or oxide, and the molybdenum salt is ammonium molybdate. The Ca source is calcium carbonate. The Ba source is barium carbonate. The Sr source is strontium carbonate. The pore-forming agent includes at least one of activated carbon, graphite, sodium hydroxymethyl cellulose and polystyrene microspheres. The amount of the pore-forming agent added is 0.01% to 5% of the mass of the metal source. Among them, the metal source is Fe source, K source, Ce source, Mo source, Ca source, and at least one selected from Ba source and Sr source, and the metal source is calculated as oxide.

[0026] The third aspect of the present invention provides use of the catalyst or the catalyst prepared by the method in the reaction of dehydrogenating ethylbenzene to prepare styrene.

[0027] According to the present invention, the application method is: a raw material containing ethylbenzene is contacted with the above catalyst of the present invention in the presence of water vapor to carry out a dehydrogenation reaction to obtain a product containing styrene.

[0028] According to the present invention, in the reaction, the weight ratio of water to ethylbenzene (hereinafter referred to as water ratio) is 0.8 to 2.5.

[0029] According to the present invention, water is preheated to become water vapor and is fully mixed with the feed gas before entering the reactor.

[0030] According to the present invention, the temperature of the dehydrogenation reaction is 550-640°C.

[0031] According to the present invention, the pressure of the dehydrogenation reaction is an absolute pressure of 20 to 100 kPa.

[0032] According to the present invention, the mass space velocity of ethylbenzene is 0.2 to 2.0 h -1 .

[0033] Compared with the prior art, the present invention has significant advantages and outstanding effects, as follows:

[0034] 1. In the catalyst of the present invention, the catalyst comprises Fe, K, Ce, Mo, Ca elements, and at least one selected from Ba and Sr; wherein the surface layer of the catalyst contains CO3 2- In the Raman spectrum of the catalyst, CO3 2- The characteristic peak intensity is 10% to 200% of the characteristic peak intensity of Fe2O3. The selectivity of Fe-K-Ce series dehydrogenation catalysts is directly related to the properties of the catalyst surface. The inventors have found that the surface of the catalyst contains a certain amount of CO3 2- The performance of the catalyst can be improved. 2- The surface properties of the catalyst were adjusted, the formation of by-product toluene was reduced, and the styrene selectivity and ethylbenzene conversion rate in the reaction were significantly improved.

[0035] In the present invention, the catalyst composition includes at least one element selected from Ba and Sr, which helps to improve the selectivity of styrene, and the effect of adding the two elements synergistically is better.

[0036] 2. In the present invention, in the preparation method of the catalyst, at least one of the metal sources is a metal carbonate, and in the drying process of the preparation method, specific relative humidity and drying temperature conditions are controlled to enrich carbonate ions on the catalyst surface, so that in the Raman spectrum, CO3 2- When the intensity of the characteristic peak is 10% to 200% of the intensity of the characteristic peak of Fe2O3, the performance of the catalyst is significantly improved.

[0037] Preferably, the ratio of Ba to Sr is limited, and the prepared catalyst has high selectivity. Furthermore, the introduction of barium carbonate and / or strontium carbonate during the catalyst preparation process also increases the CO3 2- concentration, thus improving the selectivity of styrene and the conversion rate of ethylbenzene.

[0038] 3. The catalyst of the present invention has the advantages of high styrene selectivity and high ethylbenzene conversion rate when used in the dehydrogenation of ethylbenzene to prepare styrene, and has achieved excellent technical effects.

[0039] The catalyst of the present invention is evaluated for activity in an isothermal fixed bed at 50 kPa (absolute pressure) and a mass space velocity of 0.5 h / min for ethylbenzene. -1 , 600°C, and the water ratio was reduced from the usual 2.0 (weight) to 1.2 (weight) conditions. After 100 hours of reaction, the ethylbenzene conversion rate can reach 76.2%, and the styrene selectivity can reach 98.1%. This shows that the catalyst of the present invention has high styrene selectivity and good activity when used in the reaction of ethylbenzene dehydrogenation to prepare styrene, and has achieved good technical effects. BRIEF DESCRIPTION OF THE DRAWINGS

[0040] Figure 1 The Raman spectra of the catalysts prepared in Example 1, Example 5 and Comparative Example 1 of the present invention. DETAILED DESCRIPTION

[0041] The endpoints and any values ​​of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of each range, the endpoint values ​​of each range and the individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.

[0042] In the present invention, the Raman spectrum is measured using the LabRAM Aramis model of Horiba Jobin Yvon Company, with a laser wavelength of 532nm. In the Raman spectrum of the catalyst, 1050-1075cm -1 The peak of the wavelength range is CO3 2- Characteristic diffraction peak, 660~680cm -1 The peaks in the wavelength range are the characteristic diffraction peaks of Fe2O3. 2- The ratio of the characteristic peak intensity to the characteristic peak intensity of Fe2O3 is, 2- The ratio of the height of the characteristic diffraction peak to that of the characteristic diffraction peak of Fe2O3.

[0043] In the present invention, relative humidity is defined as the ratio of the water vapor partial pressure in the gas to the saturated water vapor partial pressure under certain temperature and pressure conditions. The relative humidity of the present invention is measured using a testo 623 digital temperature and humidity recorder. The drying gas pressure is normal pressure. The test conditions for relative humidity in each example are the temperature and pressure of the catalyst drying environment in a constant humidity oven.

[0044] In the present invention, the catalyst of the present invention is used to evaluate the performance of ethylbenzene dehydrogenation reaction in a negative pressure isothermal fixed bed, and the process is briefly described as follows:

[0045] The reactor is a stainless steel tube with an inner diameter of 1", filled with 50-150 ml of catalyst with a diameter of 3-10 mm. Deionized water and ethylbenzene are respectively fed into the preheating mixer through metering pumps, and then preheated and mixed into a gaseous state before entering the reactor. The reactor is heated by an electric heating wire to reach a predetermined temperature. The reactants flowing out of the reactor are condensed with water and their composition is analyzed by a gas chromatograph.

[0046] The ethylbenzene conversion rate and styrene selectivity are calculated according to the following formula:

[0047]

[0048]

[0049] Styrene yield % = ethylbenzene conversion % * styrene selectivity %.

[0050] In the present invention, the evaluation conditions of each catalyst are as follows: 100 ml of the dehydrogenation catalyst is loaded into the reactor, and the reaction mixture is heated at 50 kPa (absolute pressure) and a mass space velocity of 0.5 h -1 The performance evaluation was carried out under the conditions of reaction temperature of 600°C and water ratio of 1.2 (wt%). The test results of reaction time of 100h are listed in Table 1.

[0051] The present invention will be further described below by way of examples, but the protection scope of the present invention is not limited by the examples.

[0052] Example 1

[0053] Weigh 74.5 parts of red iron oxide equivalent to Fe2O3, 12.0 parts of potassium carbonate equivalent to K2O, 8.2 parts of cerium nitrate equivalent to CeO2, 2.6 parts of ammonium molybdate equivalent to MoO3, 1.5 parts of calcium carbonate equivalent to CaO, 1.2 parts of barium carbonate equivalent to BaO and 2.0 parts of sodium hydroxymethyl cellulose, add them into a mixer and stir for 2 hours until they are evenly mixed. Then add deionized water accounting for 24% of the total weight of the dehydrogenation catalyst raw material and mix for 2 hours. Then extrude and pelletize the above mixture to obtain particles with a diameter of 3 mm and a length of 6 mm, put them into a constant humidity oven, dry them at a relative humidity of 70% and 65°C for 5 hours, then place them in a muffle furnace and roast them at 850°C for 4 hours to obtain a finished dehydrogenation catalyst. The composition of the dehydrogenation catalyst is listed in Table 1.

[0054] The Raman spectrum of the catalyst is Figure 1 As shown, there is CO3 on the catalyst surface 2- ,CO3 2- The characteristic diffraction peak is at 1064cm -1The characteristic diffraction peak of Fe2O3 is at 668cm -1 CO3 2- The intensity of the characteristic diffraction peak is 69% of the intensity of the characteristic diffraction peak of Fe2O3.

[0055] Example 2

[0056] Weigh 60.5 parts of red iron oxide equivalent to Fe2O3, 19.2 parts of potassium carbonate equivalent to K2O, 10.3 parts of cerium nitrate equivalent to CeO2, 4.9 parts of ammonium molybdate equivalent to MoO3, 5.0 parts of calcium carbonate equivalent to CaO, 0.1 parts of barium carbonate equivalent to BaO and 1.0 parts of sodium hydroxymethyl cellulose, add to a mixer and stir for 2 hours until mixed evenly. Then add deionized water accounting for 18% of the total weight of the dehydrogenation catalyst raw material and mix for 2 hours. Then extrude and pelletize the above mixture to obtain particles with a diameter of 3 mm and a length of 6 mm, put them into a constant humidity oven, dry them at a relative humidity of 62% and 75°C for 5 hours, then place them in a muffle furnace and roast them at 850°C for 4 hours to obtain a finished dehydrogenation catalyst. The composition of the dehydrogenation catalyst is listed in Table 1.

[0057] Example 3

[0058] Weigh 82.6 parts of red iron oxide equivalent to Fe2O3, 8.2 parts of potassium carbonate equivalent to K2O, 4.2 parts of cerium nitrate equivalent to CeO2, 2.9 parts of ammonium molybdate equivalent to MoO3, 0.2 parts of calcium carbonate equivalent to CaO, 1.9 parts of barium carbonate equivalent to BaO and 4.0 parts of sodium hydroxymethyl cellulose, add them into a mixer and stir for 2 hours until they are evenly mixed. Then add 30% of the total weight of deionized water of the dehydrogenation catalyst raw material and mix for 2 hours. Then extrude and pelletize the above mixture to obtain particles with a diameter of 3 mm and a length of 6 mm, put them into a constant humidity oven, dry them at a relative humidity of 50% and 82°C for 2 hours, then place them in a muffle furnace and roast them at 850°C for 4 hours to obtain a finished dehydrogenation catalyst. The composition of the dehydrogenation catalyst is listed in Table 1.

[0059] Example 4

[0060] Weigh 71.9 parts of red iron oxide equivalent to Fe2O3, 10.8 parts of potassium carbonate equivalent to K2O, 11.0 parts of cerium nitrate equivalent to CeO2, 0.5 parts of ammonium molybdate equivalent to MoO3, 4.6 parts of calcium carbonate equivalent to CaO, 1.2 parts of barium carbonate equivalent to BaO and 0.01 parts of sodium hydroxymethyl cellulose, add to a mixer and stir for 2 hours until mixed evenly. Then add deionized water accounting for 30% of the total weight of the dehydrogenation catalyst raw material and mix for 2 hours. Then extrude and pelletize the above mixture to obtain particles with a diameter of 3 mm and a length of 6 mm, put them into a constant humidity oven, dry them at a relative humidity of 60% and 15°C for 8 hours, then place them in a muffle furnace and roast them at 850°C for 4 hours to obtain a finished dehydrogenation catalyst. The composition of the dehydrogenation catalyst is listed in Table 1.

[0061] Example 5

[0062] Weigh 74.5 parts of red iron oxide equivalent to Fe2O3, 12.0 parts of potassium carbonate equivalent to K2O, 8.2 parts of cerium nitrate equivalent to CeO2, 2.6 parts of ammonium molybdate equivalent to MoO3, 1.5 parts of calcium carbonate equivalent to CaO, 0.6 parts of barium carbonate equivalent to BaO, 0.6 parts of strontium carbonate equivalent to SrO and 2.0 parts of sodium hydroxymethyl cellulose, add to a mixer and stir for 2 hours until mixed evenly. Then add 24% of the total weight of deionized water accounting for the total weight of the dehydrogenation catalyst raw material and mix for 2 hours. Then extrude and pelletize the above mixture to obtain particles with a diameter of 3 mm and a length of 6 mm, put them into a constant humidity oven, dry them at a relative humidity of 90% and 50°C for 5 hours, and then place them in a muffle furnace and roast them at 850°C for 4 hours to obtain a finished dehydrogenation catalyst. The composition of the dehydrogenation catalyst is listed in Table 1.

[0063] The Raman spectrum of the catalyst is Figure 1 As shown. There is CO3 on the catalyst surface 2- ,CO3 2- The characteristic diffraction peak is at 1064cm -1 The characteristic diffraction peak of Fe2O3 is at 668cm -1 CO3 2- The characteristic diffraction peak intensity is 112% of the characteristic diffraction peak intensity of Fe2O3.

[0064] Example 6

[0065] Weigh 74.5 parts of red iron oxide equivalent to Fe2O3, 12.0 parts of potassium carbonate equivalent to K2O, 8.2 parts of cerium nitrate equivalent to CeO2, 2.6 parts of ammonium molybdate equivalent to MoO3, 1.5 parts of calcium carbonate equivalent to CaO, 0.6 parts of barium carbonate equivalent to BaO, 0.6 parts of strontium carbonate equivalent to SrO and 2.0 parts of sodium hydroxymethyl cellulose, add them into a mixer and stir for 2 hours until they are evenly mixed. Then add 24% of the total weight of deionized water accounting for the total weight of the dehydrogenation catalyst raw material and mix for 2 hours. Then extrude and pelletize the above mixture to obtain particles with a diameter of 3 mm and a length of 6 mm, put them into a constant humidity oven, dry them at a relative humidity of 85% and 50°C for 5 hours, then place them in a muffle furnace and roast them at 850°C for 4 hours to obtain a finished dehydrogenation catalyst. The composition of the dehydrogenation catalyst is listed in Table 1.

[0066] Example 7

[0067] Weigh 74.5 parts of red iron oxide equivalent to Fe2O3, 12.0 parts of potassium carbonate equivalent to K2O, 8.2 parts of cerium nitrate equivalent to CeO2, 2.6 parts of ammonium molybdate equivalent to MoO3, 1.5 parts of calcium carbonate equivalent to CaO, 0.4 parts of barium carbonate equivalent to BaO, 0.8 parts of strontium carbonate equivalent to SrO and 2.0 parts of sodium hydroxymethyl cellulose, add to a mixer and stir for 2 hours until mixed evenly. Then add deionized water accounting for 24% of the total weight of the dehydrogenation catalyst raw material and mix for 2 hours. Then extrude and pelletize the above mixture to obtain particles with a diameter of 3 mm and a length of 6 mm, put into a constant humidity oven, dry for 5 hours at a relative humidity of 74% and 42°C, then place in a muffle furnace and roast at 850°C for 4 hours to obtain a finished dehydrogenation catalyst. The composition of the dehydrogenation catalyst is listed in Table 1.

[0068] Example 8

[0069] Weigh 74.5 parts of yellow iron oxide equivalent to Fe2O3, 12.0 parts of potassium carbonate equivalent to K2O, 8.2 parts of cerium nitrate equivalent to CeO2, 2.6 parts of ammonium molybdate equivalent to MoO3, 1.5 parts of calcium carbonate equivalent to CaO, 0.9 parts of barium carbonate equivalent to BaO, 0.3 parts of strontium carbonate equivalent to SrO and 2.0 parts of sodium hydroxymethyl cellulose, add to a mixer and stir for 2 hours until mixed evenly. Then add deionized water accounting for 24% of the total weight of the dehydrogenation catalyst raw material and mix for 2 hours. Then extrude and pelletize the above mixture to obtain particles with a diameter of 3 mm and a length of 6 mm, put them into a constant humidity oven, dry them at a relative humidity of 68% and 30°C for 5 hours, and then place them in a muffle furnace and roast them at 850°C for 4 hours to obtain a finished dehydrogenation catalyst. The composition of the dehydrogenation catalyst is listed in Table 1.

[0070] Comparative Example 1

[0071] Weigh 75.7 parts of red iron oxide equivalent to Fe2O3, 12.0 parts of potassium nitrate equivalent to K2O, 8.2 parts of cerium nitrate equivalent to CeO2, 2.6 parts of ammonium molybdate equivalent to MoO3, 1.5 parts of calcium hydroxide equivalent to CaO, 0.6 parts of barium nitrate equivalent to BaO, 0.6 parts of strontium nitrate equivalent to SrO and 2.0 parts of sodium hydroxymethyl cellulose, add to a mixer and stir for 2 hours until mixed evenly. Add deionized water accounting for 24% of the total weight of the dehydrogenation catalyst raw materials and mix for 2 hours. Then extrude and pelletize the above mixture to obtain particles with a diameter of 3 mm and a length of 6 mm, put them into a constant humidity oven, dry them at a relative humidity of 90% and 50°C for 5 hours, then place them in a muffle furnace and roast them at 850°C for 4 hours to obtain the finished dehydrogenation catalyst. The composition of the dehydrogenation catalyst is listed in Table 1. The Raman spectrum of the catalyst is shown in Figure 1 shown.

[0072] Comparative Example 2

[0073] Same as Example 5, except that the drying conditions are 10% relative humidity and 95° C. for 3 h.

[0074] Table 1 Catalyst compositions and evaluation results of Examples and Comparative Examples

[0075]

[0076]

[0077] The above describes the specific implementation of the present invention in detail, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the various technical features being combined in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.

Claims

1. An ethylbenzene dehydrogenation catalyst, comprising Fe, K, Ce, Mo, Ca elements, and at least one selected from Ba and Sr; wherein: The surface layer of the catalyst contains CO3 2- In the Raman spectrum of the catalyst, CO3 2- The intensity of the characteristic diffraction peak is 10% to 200% of the intensity of the characteristic diffraction peak of Fe2O3.

2. The catalyst according to claim 1, characterized in that CO3 2- The characteristic diffraction peak intensity is 80% to 120% of the characteristic diffraction peak intensity of Fe2O3.

3. The catalyst according to claim 1, characterized in that The catalyst, based on the mass of the catalyst and calculated as oxide, comprises the following components: (a) 60% to 83% Fe2O3; (b) 8% to 20% K2O; (c) 4% to 11% CeO2; (d) 0.5% to 5% MoO3; (e) 0.2% to 5% CaO; (f) 0.1% to 2% of BaO and / or SrO.

4. The catalyst according to claim 1, characterized in that The catalyst includes both Ba and Sr elements; calculated as oxides, the mass ratio of BaO to SrO is 0.2 to 3:1, preferably 0.5 to 3:

1.

5. A method for preparing the catalyst according to any one of claims 1 to 4, characterized in that: include: The ethylbenzene dehydrogenation catalyst is obtained by mixing Fe source, K source, Ce source, Mo source, Ca source, at least one selected from Ba source and / or Sr source, and an optional pore-forming agent, and then drying, molding, and calcining; at least one of the catalyst raw material metal sources is a metal carbonate.

6. The preparation method according to claim 5, characterized in that: The drying conditions are: temperature of 10-90° C., preferably 20-60° C.; and / or time of 0.5-10 h, preferably 1-8 h; and / or relative humidity of 50%-100%, preferably 60%-99%.

7. The preparation method according to claim 5, characterized in that: The calcination conditions are: a calcination temperature of 700 to 1000° C., preferably 750 to 950° C.; and / or a calcination time of 0.5 to 10 hours, preferably 2 to 6 hours.

8. The preparation method according to claim 5, characterized in that: The catalyst raw material metal source is added in the form of metal salt and / or metal oxide; Furthermore, the Fe source is added in the form of Fe2O3 oxide; the Fe source is preferably selected from red iron oxide and / or yellow iron oxide; And / or, the K source is potassium carbonate; And / or, the Ce source is any one or more of cerium nitrate, cerium oxalate, and cerium carbonate; And / or, the Mo source is ammonium molybdate; And / or, the Ca source is calcium carbonate; And / or, the Ba source is barium carbonate; And / or, the Sr source is strontium carbonate; And / or, the pore-forming agent includes at least one of activated carbon, graphite, sodium hydroxymethyl cellulose and polystyrene microspheres; preferably, the added amount of the pore-forming agent is 0.01% to 5% of the mass of the metal source.

9. Use of the catalyst according to any one of claims 1 to 4 or the catalyst prepared by the method according to any one of claims 5 to 8 in the dehydrogenation of ethylbenzene to produce styrene.

10. The use according to claim 9, characterized in that: In the reaction, the weight ratio of water to ethylbenzene is 0.8 to 2.5; and / or, the reaction temperature is 550 to 640° C.; and / or, the reaction pressure is an absolute pressure of 20 to 100 kPa; and / or, the mass space velocity of ethylbenzene is 0.2 to 2.0 h -1 .

Citation Information

Patent Citations

  • Catalyst for preparing styrene through ethylbenzene dehydrogenation

    CN105056966A

  • Catalyst for ethylbenzene dehydrogenation for preparing styrene

    CN105478130A

  • Dehydrogenation catalyst for preparing styrene, preparation method and application thereof, and ethylbenzene dehydrogenation method

    CN114425359A

  • Deoxidizing catalyst for producing alkyl thiazolinyl aromatic hydrocarbon

    CN1490083A

  • Catalyst for preparing styrene by ethylbenzene dehydrogenation and preparation method thereof

    WO2013159251A1